Mobile mechanical signal generator for macrophage polarization - Jiamiao Jiang; Fei Wang; Weichang Huang; Jia Sun; Yicheng Ye; Juanfeng Ou; Meihuan Liu; Junbin Gao; Shuanghu Wang; Dongmei Fu; Bin Chen; Lu Liu; et al. (Exploration, 2023)
Abstract The importance of mechanical signals in regulating the fate of macrophages is gaining increased attention recently. However, the recently used mechanical signals normally rely on the physical characteristics of matrix with non‐specificity and instability or mechanical loading devices with uncontrollability and complexity. Herein, we demonstrate the successful fabrication of self‐assembled microrobots (SMRs) based on magnetic nanoparticles as local mechanical signal generators for precise macrophage polarization. Under a rotating magnetic field (RMF), the propulsion of SMRs occurs due to the elastic deformation via magnetic force and hydrodynamics. SMRs perform wireless navigation toward the targeted macrophage in a controllable manner and subsequently rotate around the cell for mechanical signal generation. Macrophages are eventually polarized from M0 to anti‐inflammatory related M2 phenotypes by blocking the Piezo1‐activating protein‐1 (AP‐1）‐CCL2 signaling pathway. The as‐developed microrobot system provides a new platform of mechanical signal loading for macrophage polarization, which holds great potential for precise regulation of cell fate.‐